Progestin-Primed Ovarian Stimulation with Clomiphene Citrate Supplementation May Be More Feasible for Young Women with Diminished Ovarian Reserve Compared with Standard Progestin-Primed Ovarian Stimulation: A Retrospective Study - Lin Y; Chen Q; Zhu J; Teng Y; Huang X; Chen X (Dove Medical Press, 2021)
Yue Lin,* Qianqian Chen,* Jing Zhu, Yili Teng, Xuefeng Huang, Xia Chen Reproductive Medicine Center, First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, People's Republic of China*These authors contributed equally to this workCorrespondence: Xia Chen; Xuefeng HuangReproductive Medicine Center, First Affiliated Hospital of Wenzhou Medical University, 96 Fuxue Road, Wenzhou, Zhejiang, People's Republic of ChinaTel +86-577-88069380Email chenxia96sz@163.com; xuefhuang0711sz@126.comPurpose: The present study was designed to compare the efficiency of the progestin-primed ovarian stimulation (PPOS) protocol with clomiphene citrate (CC) supplementation (PPOS+CC) and the standard PPOS protocol for women of different ages with diminished ovarian reserve (DOR).Patients and Methods: This retrospective cohort study included 364 DOR women who underwent controlled ovarian stimulation with PPOS+CC (n = 223) or standard PPOS (n = 141). They were divided into subgroups based on age: ≤ 35 years and > 35 years. Differences in baseline characteristics, ovarian stimulation characteristics, endocrinological characteristics, and clinical outcome between the two groups were assessed. Statistical analyses were stratified by age.Results: In all women with DOR, PPOS+CC was associated with a lower percentage of women with profound pituitary suppression than standard PPOS (0.0% vs 18.6%, P < 0.001 and 1.3% vs 11.0%, P = 0.002). In young women with DOR, more high-quality cleavage-stage embryos were harvested (1.96 vs 1.38, P = 0.018) and a lower dosage of gonadotropin per oocyte retrieved was required (558.37 vs 909.82, P = 0.036) in PPOS+CC. In older women with DOR, PPOS+CC led to an increase in the incidence of luteinizing hormone (LH) surge levels above 10 IU/L on trigger day (12.7% vs 4.9%, P = 0.028) and a decrease in the rate of oocyte maturation (84.7% vs 89.9%, P = 0.034) compared to standard PPOS.Conclusion: Clomiphene citrate is an effective adjuvant to alleviate pituitary suppression in PPOS protocols; for young women with DOR, CC supplementation had a positive impact on the number of high-quality embryos. However, older women with DOR would be at risk of developing a premature LH surge and having poor oocyte maturation rate under the PPOS+CC protocol.Keywords: diminished ovarian reserve, clomiphene citrate, medroxyprogesterone acetate, controlled ovarian stimulation, in vitro fertilization, luteinizing hormone surge